2010
DOI: 10.1111/j.1872-034x.2009.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver function parameters after percutaneous radiofrequency ablation therapy in patients with hepatocellular carcinoma

Abstract: Liver function parameters, particularly serum albumin level, gradually and dominantly decreased in HCC patients with grade B and C according to the CPs classification over the course of 1 year after RFA therapy. A CPs of 9 or more represents a major risk factor for the aggravation of liver function after RFA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…For example, Koda et al [10] reported that liver function in patients with low pre-treatment CP scores transiently deteriorated within the first month of observation, while patients with high pre-treatment CP scores exhibited a greater extent of deterioration over a longer term of observation, approximately 6 mo. In a study by Kuroda et al [11] , changes in liver function were monitored one year after RFA, and it was observed that a CP score of 9 or higher represented a major risk factor for aggravation of liver function following RFA. Furthermore, in another report by Yokoyama et al [12] , the influence of RFA treatments on long-term liver function was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Koda et al [10] reported that liver function in patients with low pre-treatment CP scores transiently deteriorated within the first month of observation, while patients with high pre-treatment CP scores exhibited a greater extent of deterioration over a longer term of observation, approximately 6 mo. In a study by Kuroda et al [11] , changes in liver function were monitored one year after RFA, and it was observed that a CP score of 9 or higher represented a major risk factor for aggravation of liver function following RFA. Furthermore, in another report by Yokoyama et al [12] , the influence of RFA treatments on long-term liver function was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is currently recognized as an effective local treatment for HCC [5,6] and has been shown to be a relatively low risk procedure [7][8][9] . However, deterioration of liver function has been observed during the long-term follow-up of these patients [10][11][12] . Therefore, the risk factors that contribute to deterioration of liver function need to be identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the majority of patients, HCC generally develops against a background of liver cirrhosis. RFA against HCC sometimes worsens the liver parenchymal function (6). Deterioration of the liver function after RFA is problematic because HCC patients experience a high incidence of recurrence due to the development of minor intrahepatic metastasis and multicentric carcinogenesis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Few reports on the safety and effectiveness of RFA for patients with poor liver function exist; this leads to difficulty in taking treatment-related decisions [16]. Therefore, we analyzed the outcomes and changes in liver function after RFA was used to treat HCC patients with Child-Pugh B/C liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%